EFEKTIFITAS REBUSAN DAUN KERSEN (Muntingia calabura L) UNTUK MENURUNKAN KADAR GULA DARAH TERHADAP PENDERITA DIABETES MILITUS DI DESA KEDUNG RINGIN GIRIPURWO WONOGIRI - Kristiana Puji Purwandari; Lilis Suryaningsih (Jurnal Keperawatan GSH, 2021)
A healthy lifestyle describes daily behavioral patterns that lead to efforts to maintain physical, mental, social conditions in a positive state. A healthy lifestyle includes sleeping, eating, controlling weight, not smoking, or drinking alcohol, exercising regularly and skillfully in managing stress experienced by Lisnawati (2006). This study aims to determine the effect oflifestyle with quality of life in the elderly. The method used in this research is the descriptive research method conducted at Wonogiri Nursing Home. From the results of statistical data processing shows that 14 respondents (100%) have a good quality of life. There is an influence of the lifestyle of the elderly with the quality of life in Wonogiri Nursing Home. Background: Diabetes Militus is a chronic disease that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively produce insulin that is needed this condition can occur Hyperglycemia. Hyperglycemia is a state of increased blood glucose levels in a person's body that exceeds normal levels. High blood sugar levels in Diabetes Militus patients can be overcome with pharmacological and non pharmacological therapies. One of the non-pharmacological therapies is the Granting Therapy of Cherry leaves (Muntingia calabura L). Purpose: To determine the effectiveness of cherry leaves decoction (muntingiacalabura l) to reduce blood sugar levels in patients with diabetes mellitus in the village of Kedung Ringin Giripurwo Wonogiri Method: This research method using research study method (case study), sampling using purposive sampling with a sample size of 5 respondents. Results: The results of this study indicate a decrease in blood pressure in all three respondents. Conclusion: There is a significant effect of Kersen leaf decoction therapy (muntingia calabura l) to reduce blood sugar levels in diabetics in Kedung Ringin Giripurwo Wonogir village. Latar belakang : Diabetes Militus adalah penyakit kronis yang terjadi baik ketika pankreas tidak menghasilkan cukup insulin atau ketika tubuh tidak dapat secara efektif menghasilkan insulin yang diperlukan kondisi ini dapat terjadi Hiperglikimia. Hiperglikemia merupakan suatu keadaan meningkatnya kadar glukosa darah dalam tubuh seseorang yang melebihi kadar normal. Kadar gula darah yang tinggi pada pasien Diabetes Militus dapat diatasi dengan terapi farmakologis dan non farmakologis. Salah satu terapi non farmakologis adalah Terapi Pemberian Rebusan Daun kersen (Muntingia calabura L).Tujuan : Untuk mengetahui Efektifitas rebusan daun kersen (muntingia calabura l) untuk menurunkan kadar gula darah terhadap penderita diabetes militus di desa kedung ringin giripurwo wonogiri Metode : Metode penelitian ini menggunakan metodecase study research (studi kasus), pengambilan sampel menggunakan sampling purposive dengan jumlah sample sebanyak 5 responden.Hasil : Hasil penelitian ini menunjukkan adanya penurunan tekanan darah pada ketiga responden. Kesimpulan : Ada pengaruh yang signifikan Terapi Rebusan daun Kersen (muntingia calabura l) untuk menurunkan kadar gula darah terhadap penderita diabetes militus di desa kedung ringin giripurwo wonogiri